Pengembangan Modul Manajemen Sekolah Aman Bencana untuk SMP di Kabupaten Temanggung - Nurul Azizah Desi Wulandari; Rahmat Mulyono; Jumintono Jumintono (Media Manajemen Pendidikan, 2026)
Schools located in disaster-prone areas face substantial risks to the safety of school communities and the continuity of learning processes, requiring systematic and well-planned management to enhance preparedness. This study aimed to develop a disaster-safe school management model to improve school preparedness in accordance with the School-Based Disaster Preparedness Program (Satuan Pendidikan Aman Bencana/SPAB). This study employed a Research and Development (R&D) approach encompassing needs analysis, product design and development, expert validation, revision, and limited field testing. The research subjects included school principals, teachers, and educational staff from disaster-prone areas. Data were collected through interviews, questionnaires, and document analysis and analyzed using qualitative and quantitative descriptive techniques. The findings indicate that disaster preparedness management has not been fully integrated into educational management functions, particularly in planning, implementation, and evaluation. The developed model covers four key areas: facilities and infrastructure, curriculum, financial management, and human resources. Expert and practitioner evaluations confirmed that the model is feasible and has the potential to enhance school preparedness. Therefore, this model may serve as a practical reference for strengthening SPAB implementation in disaster-prone educational settings.